যদি \((\sqrt{a}+\sqrt{b})\propto (\sqrt{a}-\sqrt{b})\) হয়, তবে দেখাও যে \((a+b)\propto \sqrt{ab}\)
Madhyamik 2024
\((\sqrt{a}+\sqrt{b})\propto (\sqrt{a}-\sqrt{b})\)
বা, \((\sqrt{a}+\sqrt{b}) = k(\sqrt{a}-\sqrt{b})\) [ \(k\) অশূন্য ভেদ ধ্রুবক]
বা, \(\cfrac{\sqrt{a}+\sqrt{b}}{\sqrt{a}-\sqrt{b}}=k\)
বা, \(\cfrac{(\sqrt{a}+\sqrt{b})^2}{(\sqrt{a}-\sqrt{b})^2}=k^2\) [উভয়পক্ষের বর্গ করে পাই]
বা, \(\cfrac{a+b+2\sqrt{ab}}{a+b-2\sqrt{ab}}=k^2\)
বা, \(\cfrac{(a+b+2\sqrt{ab})+(a+b-2\sqrt{ab})}{(a+b+2\sqrt{ab})-(a+b-2\sqrt{ab})}=\cfrac{k^2+1}{k^2-1}\) [যোগভাগ পক্রিয়া করে পাই ]
বা, \(\cfrac{\cancel{2}(a+b)}{\cancel{4}2\sqrt{ab}}=\cfrac{k^2+1}{k^2-1}\)
বা, \(\cfrac{(a+b)}{\sqrt{ab}}=\cfrac{2(k^2+1)}{(k^2-1)}=\) ধ্রুবক
\(\therefore (a+b)\propto \sqrt{ab}\) [প্রমাণিত ]